Transformasi Sampah Plastik Menjadi Paving Block sebagai Upaya Pengelolaan Sampah Berkelanjutan di Desa Laut Biru - Faizal Kasim (Institut Pertanian Bogor, 2025)
The waste management training program for paving block production in Laut Biru Village aims to enhance community awareness and skills in sustainable plastic waste management. This program focused on transforming plastic waste into paving blocks as a waste management solution and an effort to support a circular economy. The methodology included observational surveys, program formulation through Focus Group Discussions (FGD), training implementation, as well as evaluation and monitoring. The initial results demonstrated an increase in community awareness of integrated waste management and environmental sustainability. Evaluations showed that 61.54% of the participants recognized paving block technology as a viable waste solution, while 84.62% showed improved awareness of the dangers of plastic waste. This initial success highlights the significant potential of reducing plastic waste and improving community economic welfare. Further recommendations include capacity enhancement, integration with BUMDes, and government policy support. Collaboration with local organizations can expand the impact of the program and establish a more effective waste management system. With the strategic implementation of these measures, Laut Biru Village has the potential to become a model for integrated waste management in other coastal villages.